Estudo de caso sobre a educação ambiental nas escolas do meio rural, em Santana do Livramento/RS - Paust, Kathleen da Silva (2023)
In view of the importance of Environmental Education as a way of mitigating the negative consequences related to climate change, Resolution No. 363 of 2021 was instituted by the State Education Commission of Rio Grande do Sul (RS). It contains the curricular guidelines for environmental education in RS. Education has a transforming role in society, in which rural education seeks to value traditional knowledge and fight against the hegemony imposed by the current capitalist system. Thus, the objective of the work was to identify the main macrotrend of environmental education being developed in eight rural schools in Santana do Livramento/RS. For this, a descriptive-exploratory research was carried out in eight schools in the rural area of the municipality of Santana do Livramento (RS) through interviews and analysis of the political pedagogical projects of each of the schools. Afterwards, a content analysis of the transcription of the interviews and a documental analysis of the Political Pedagogical Projects (PPP) of the schools were carried out. In the schools' PPPs, principles and concepts of the macrotrend of critical environmental education were found, however the practices aimed at environmental education were predominantly conservative and pragmatic.